Wind power integration : connection and system operational aspects - Fox, Brendan (Institution of Engineering and Technology, 2007)
The rapid growth of wind power and the implications of this on future power system planning, operation and control has become an even greater challenge in today's liberated electricity market conditions. This essential new book examines the main problems of wind power integration and guides the reader through a number of the most recent solutions based on current research and operational experience of wind power integration.
"The book arose largely from a number of workshops organised as part of an EPSRC ... network on 'Operation of power systems with significant wind power import' ... later known simply as BLOWING (Bringing Large-scale Operation of Wind power Into Networks and Grids)"--Page x
Keywords: Wind power.; elektronické knihy; electronic books